Parkinson’s Disease With Psychosis: A Case Report of Neuropsychiatric Manifestations - Aung Sein; Mobolape Olajide; Rachel Rajaratnam; Lior Mevorach; Sakshi Alewad (BJPsych Open)
Aims: Parkinson’s disease (PD) is mainly a movement disorder, although 30% of PD patients may also suffer from psychosis, which may impair quality of life. PD psychosis (PDPsy) may result following approximately 10 years of treatment using dopaminergic agonists. PDPsy is characterized by recurrent and continuous hallucinations and delusions lasting for at least 1 month.